Induced pluripotent stem cells (iPSCs): Where are we and where are we heading? Induced pluripotent stem cells - Jamal, Arshad (Cellular and Molecular Biology, 2023)
Induced Pluripotent Stem Cells (iPSCs) offer a unique therapeutic tool. The extent of the ongoing clinical studies substantiates the role of these cells in a highly promising area of personalized medicine. The employment of this technology in translational research is on the horizon. However, still, many questions remain unanswered. In this review, we discussed certain challenges and difficulties currently faced during the safe and stable clinical application of iPSCs. Furthermore, we describe the potential therapeutic scenarios employing iPSCs for the betterment of human health and the improvement of the health care sector.